벼에서 CRISPR/Cas9 활용 고빈도 유전자 편집 방법 - 정유진(Yu Jin Jung); 배상수(Sangsu Bae); 이긍주(Geung-joo Lee); 서필준(Pil Joon Seo); 조용구(Yong-gu Cho); 강권규(Kwon Kyoo (Journal of plant biotechnology, 2017)
The CRISPR/Cas9 is a core technology that can result in a paradigm for breeding new varieties. This study describes in detail the sgRNA design, vector construction, and the development of a transgenic plant and its molecular analysis, and demonstrates how gene editing technology through the CRISPR/Cas9 system can be applied easily and accurately. CRISPR/Cas9 facilitates targeted gene editing through RNA-guided DNA cleavage, followed by cellular DNA repair mechanisms that introduce sequence changes at the site of cleavage. It also allows the generation of heritable-targeted gene mutations and corrections. Here, we present detailed procedures involved in the CRISPR/Cas9 system to acquire faster, easier and more cost-efficient gene edited transgenic rice. The protocol described here establishes the strategies and steps for the selection of targets, design of sgRNA, vector construction, and analysis of the transgenic lines. The same principles can be used to customize the versatile CRISPR/Cas9 system, for application to other plant species. CRISPR/Cas9 기술은 생명공학을 활용한 신품종 작물육성에 있어 패러다임 변혁을 가져다 줄 핵심 기반기술이다. 본 연구에서는 CRISPR/Cas9를 이용하여 유전자편집기술을 기존에 알려진 방법보다 쉽고 정확하게 실험 할 수 있도록 sgRNA 디자인, 벡터구축, 형질전환체 육성 및 분석 등을 자세히 기술하였다. sgRNA는 http://www.rgenome.net/ 사이트에서 NGG 영역을 중심으로 하여 target-up: 5'-ggcaGNNNNNNNNNNNNNNNNNNNN-3'과 target-down: 5'-aaacNNNNNNNNNNNNNNNNNNNNC-3'의 올리고를 디자인하였다. 식물형질전환용 벡터는 pPZP-Cas9-RGEN을 기본으로 하였으며, sgRNA의 프로모터는 OsU3를 이용하여 pPZP::35S::Cas9::PinII-OsU3::sgRNA::Bar-Gen 순으로 구축하였다. 형질전환체의 육성은 단기형질전환 Agrobacterium 법을 사용하였으며 재분화 식물체를 얻는데48일 정도 소요되었다. 형질전환체 유무는 genomic PCR 분석으로 single copy 선발은 TaqMan PCR로 분석하였다. 정밀유전자편집 식물체는 T1 세대에서 T-DNA 삽입되지 않은 식물체를 Bar-strip에 의해 선발하였다. 선발된 식물체의 sgRNA 영역의 염기배열 조사에 의해 유전자 편집 식물체를 육성하였다. 따라서 본 연구에서 CRISPR/Cas9 system에 의한 정밀유전자편집 기술을 이용하여 보다 빠르고 쉽고 경제적으로 유전자가 편집된 개체를 확보할 수 있었다. 본 실험에서 확립된 system은 상업용 식물 계통육성에 이용 가능하여 육종적 가치가 매우 클 것으로 사료된다.